-49-7x=9x+17

Simple and best practice solution for -49-7x=9x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49-7x=9x+17 equation:


Simplifying
-49 + -7x = 9x + 17

Reorder the terms:
-49 + -7x = 17 + 9x

Solving
-49 + -7x = 17 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-49 + -7x + -9x = 17 + 9x + -9x

Combine like terms: -7x + -9x = -16x
-49 + -16x = 17 + 9x + -9x

Combine like terms: 9x + -9x = 0
-49 + -16x = 17 + 0
-49 + -16x = 17

Add '49' to each side of the equation.
-49 + 49 + -16x = 17 + 49

Combine like terms: -49 + 49 = 0
0 + -16x = 17 + 49
-16x = 17 + 49

Combine like terms: 17 + 49 = 66
-16x = 66

Divide each side by '-16'.
x = -4.125

Simplifying
x = -4.125

See similar equations:

| D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 | | -14=(2/5)(9-2b) |

Equations solver categories